Ensamble de batoideos costeros en el norte del Perú: Conocimiento preliminar - González-Pestana, Adriana; Molina-Salgado, Pamela; Ponce, Alvaro (Revista de Biología Marina y Oceanografía, 2023)
Abstract.- This preliminarily study aims at increasing our understanding of an assemblage of coastal batoids on the northern coast of Peru by determining species composition, body size structure and its behaviour in marine-coastal zone of Los Órganos, Piura Region, Peru. During 20 field trips, between the years 2016, 2017, and 2019, eighty-six individuals were sampled belonging to eight species: Zapteryx xyster (n= 22), Narcine entemedor (n= 11), Urobatis tumbesensis (n= 7), Urotrygon chilensis (n= 40), Pseudobatos planiceps (n= 1), Urobatis halleri (n= 1), Gymnura crebripunctata (n= 2), Aetobatus laticeps (n= 2). In the study area, a predominance of adult females was observed for Z. xyster, N. entemedor and U. chilensis. These preliminary results suggest that during the morning some batoid species (i.e., Z. xyster, N. entemedor, U. chilensis) use the coastal zone to rest since they are found inactive and partially or totally buried in the sand - N. entemedor could be also hunting through ambush. Future studies should determine if this is a gestation area for some of these batoid species.